EARLY RETINAL MICROVASCULAR ABNORMALITIES IN YOUNG ADULTS WITH TYPE 1 DIABETES MELLITUS WITHOUT CLINICALLY EVIDENT DIABETIC RETINOPATHY. Issue 7 (July 2021) - Chen, Yun-Ju; Khouri, Albert S.; Zarbin, Marco A.; Szirth, Bernard C.
Abstract : Purpose: To characterize the early retinal microvascular changes in young adults (age: 22.69 ± 3.50 years) with Type 1 diabetes mellitus without clinically detectable diabetic retinopathy using optical coherence tomography angiography and investigate the associated factors. Methods: A total of 36 participants with Type 1 diabetes mellitus (70 eyes) and 34 healthy controls (57 eyes) were retrospectively reviewed. The analyzed optical coherence tomography angiography indices included capillary vessel density, foveal avascular zone area/perimeter/acircularity index, and foveal vascular density, acquired in the 6 × 6-mm 2 area centered on the fovea. The generalized estimation equations model was applied to compare the mean values and to study the associated factors. Results: In subjects with diabetes, statistically significant decreases were observed in parafoveal vessel density in both superficial and deep capillary plexuses, foveal avascular zone area/perimeter, and foveal vascular density when compared with controls (all P < 0.05). Higher glycated hemoglobin level was independently associated with the decrease of parafoveal vessel density as well as the increase of foveal avascular zone area/perimeter (all P < 0.05). Prepubescent onset of diabetes mellitus was also independently associated with the decrease of superficial parafoveal vessel density, foveal avascular zone area/perimeter, and foveal vascular density ( P = 0.015, 0.011, 0.015, and 0.001, respectively). Conclusion: In young adults with Type 1 diabetes mellitus lacking clinical signs of diabetic retinopathy, optical coherence tomography angiography revealed alterations in retinal microvasculature that were associated with glycated hemoglobin level and onset of diabetes mellitus related to puberty. Abstract : Preceding clinically detectable diabetic retinopathy, retinal microvascular changes were detected on optical coherence tomography angiography in young adults with type 1 diabetes mellitus. Combined with other associated factors such as glycated hemoglobin and prepubescent onset of diabetes mellitus, the optical coherence tomography angiography findings may serve as early imaging markers.